2021
DOI: 10.21595/jve.2020.21487
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of transverse vibration of wire rope in flexible hoisting system

Abstract: Taking the flexible hoisting system as the research object, the transverse vibration mathematical model of the steel wire rope of the winding hoisting system is established, and the transverse vibration displacement, velocity and acceleration of the steel wire rope at 18 m away from one end of the wire rope under the sine excitation at other end is obtained through the comparison and verification of the results from the mathematical model, mechanical model and experiment. The results show that: for the length … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 7 publications
0
6
0
Order By: Relevance
“…12 Wu et al employed ANSYS FLUENT 14.5 to study the vibration of the rope of conveyances under different speeds of ventilation air. 13 The results indicated that the ventilation affected the horizontal displacement of conveyance greatly. However, this research simulated the effect of different ventilation air speeds on the rope without experimental verification.…”
Section: Introductionmentioning
confidence: 97%
See 1 more Smart Citation
“…12 Wu et al employed ANSYS FLUENT 14.5 to study the vibration of the rope of conveyances under different speeds of ventilation air. 13 The results indicated that the ventilation affected the horizontal displacement of conveyance greatly. However, this research simulated the effect of different ventilation air speeds on the rope without experimental verification.…”
Section: Introductionmentioning
confidence: 97%
“…9 Wu et al established the transversal vibration dynamic model of the steel rope of the hoisting system, and obtained the transverse vibration displacement of the rope at a point in the rope under the sine excitation at the end of the rope. 10 It concluded that the transverse vibration frequency increases when the length of the rope reduces. Guo et al investigated the nonlinear dynamic responses of the rope under periodic excitation in the hoisting system with experiments of different periodic excitation frequencies.…”
Section: Introductionmentioning
confidence: 98%
“…The intensification of the transverse displacement at the sheave tangent point increases the instability of the friction force. Wu et al [8][9]used Galerkin's discretization method to obtain the transverse vibration displacements, velocities, and accelerations of the wire rope in the hoisting system of the deep mine. The experiments demonstrated that as the external excitation frequency increases, the transverse vibration displacement of the wire rope also increases.…”
Section: Introductionmentioning
confidence: 99%
“…Compared to a fixed guide hoisting system, a rope guide hoisting system has some advantages, such as less resistance to ventilation air flows, shorter installation times, lower capital costs and reduced maintenance requirements [1][2][3]. however, affected by the mine ventilation, tension and conveyance loading quality, etc., the lateral oscillation behaviour of rope guided conveyances is so complex that the rope guided hoisting system hasn't been understood thoroughly [4][5][6]. There are few systematic research reports, and the rope guided hoisting system is lacking a complete design guideline [7].…”
Section: Introductionmentioning
confidence: 99%